2023
DOI: 10.32604/csse.2023.030556
|View full text |Cite
|
Sign up to set email alerts
|

Sailfish Optimization with Deep Learning Based Oral Cancer Classification Model

Abstract: Recently, computer aided diagnosis (CAD) model becomes an effective tool for decision making in healthcare sector. The advances in computer vision and artificial intelligence (AI) techniques have resulted in the effective design of CAD models, which enables to detection of the existence of diseases using various imaging modalities. Oral cancer (OC) has commonly occurred in head and neck globally. Earlier identification of OC enables to improve survival rate and reduce mortality rate. Therefore, the design of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The results of this study also revealed that AI has important applications in disease screening. AI can have a major role in the screening process, by supporting the screening process and staging, as categorized as the third theme entitled "screening" (43)(44)(45)(46)(47)(48). Screening is an important stage in decision making for disease management and future stages of intervention and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study also revealed that AI has important applications in disease screening. AI can have a major role in the screening process, by supporting the screening process and staging, as categorized as the third theme entitled "screening" (43)(44)(45)(46)(47)(48). Screening is an important stage in decision making for disease management and future stages of intervention and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Other research is described in Ref. [10] also introduced a groundbreaking algorithm that skillfully employs the Apriori algorithm in conjunction with a multi-ensemble algorithm that merges AdaBoost and Random Forest. This innovative approach was carefully designed to improve the precision of the fetal health classification using CTG, directly addressing the challenges posed by ambiguous data classes often seen in pregnancy.…”
Section: A Existing Algorithmsmentioning
confidence: 99%
“…5% using normalization and random forest (Norm+RF). Duhayyim et al [10] utilized SMOTE+AdaBoost to achieve a remarkable accuracy of 99%, and Raihen & Akter [11] achieved an accuracy of 85.98% using bootstrap aggregating (Bagging). Additionally, Salini et al [12] documented a 93% accuracy with feature selection and Random Forest (FS+RF).…”
Section: E Proposed Algorithm Vs Previous Studies (Stage 3)mentioning
confidence: 99%
“…al. [50] introduced a diagnosis system for the detection of oral cancer as benign or malignant from white light images, where a fusion-based feature extractor was considered and passed into an extreme learning machine (ELM) for categorization. The performance was notable but efficacy could be further improved and the issue of overfitting also needs to be clarified.…”
Section: Introductionmentioning
confidence: 99%